The vital role of nurses in alleviating anxiety in hemodialysis patients - Matulessy, Thomas (Indonesian Journal of Health Services, 2025)
Anxiety is a common psychological burden experienced by patients with chronic kidney disease undergoing hemodialysis. The prolonged dialysis procedures, lifelong dependence on dialysis machines, and uncertainty regarding future health conditions contribute to significant emotional distress among patients. In clinical practice, however, psychological aspects often receive less attention compared to the management of physical conditions. Untreated anxiety may negatively affect patients’ quality of life and adherence to treatment. This article highlights the importance of the nursing role in recognizing, understanding, and alleviating anxiety among hemodialysis patients through a holistic nursing approach. Nurses occupy a strategic position as they interact most frequently and continuously with patients during dialysis sessions. Through therapeutic communication, empathy, and psychosocial interventions such as relaxation techniques, patient education, and emotional support, nurses can help patients manage anxiety more effectively. Nevertheless, several challenges remain, including limited human resources, high workload, and insufficient institutional support for psychosocial care in dialysis settings. Strengthening nurses’ competencies in therapeutic communication and emotional support, alongside institutional commitment to integrating psychosocial care into routine dialysis services, is essential to promote patient-centered care. Enhancing the nursing role in addressing psychological needs is expected to improve the quality of life and psychological well-being of patients undergoing hemodialysis.